2018
DOI: 10.1007/s00221-018-5269-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term music training modulates the recalibration of audiovisual simultaneity

Abstract: To overcome differences in physical transmission time and neural processing, the brain adaptively recalibrates the point of simultaneity between auditory and visual signals by adapting to audiovisual asynchronies. Here, we examine whether the prolonged recalibration process of passively sensed visual and auditory signals is affected by naturally occurring multisensory training known to enhance audiovisual perceptual accuracy. Hence, we asked a group of drummers, of non-drummer musicians and of non-musicians to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 57 publications
3
22
2
5
Order By: Relevance
“…Recent reviews have shown considerable variation in task performance according to stimulus modality, inter-individual differences, age, as well as subjective states (Arstila and Lloyd, 2014 ; Wykowska and Arstila, 2014 ). Interestingly, musical training has been shown to influence audiovisual simultaneity judgments (Jicol et al, 2018 ), suggesting that long-term training modulate musician's ability to integrate audiovisual information concurrently. Recently, audiovisual simultaneity has been linked to phase resetting in the EEG beta band (Kambe et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have shown considerable variation in task performance according to stimulus modality, inter-individual differences, age, as well as subjective states (Arstila and Lloyd, 2014 ; Wykowska and Arstila, 2014 ). Interestingly, musical training has been shown to influence audiovisual simultaneity judgments (Jicol et al, 2018 ), suggesting that long-term training modulate musician's ability to integrate audiovisual information concurrently. Recently, audiovisual simultaneity has been linked to phase resetting in the EEG beta band (Kambe et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews have shown considerable variation in task performance according to stimulus modality, inter-individual differences, age, as well as subjective states [2], [63]. Interestingly, musical training has been shown to influence audiovisual simultaneity judgments [27], suggesting that long-term training modulate musician’s ability to integrate audiovisual information concurrently. Recently, audiovisual simultaneity has been linked to phase resetting in the EEG beta band [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies have used electroencephalography (EEG) and magnetoencephalography, in order to get a finer temporal understanding of neuronal activity during improvisation. Studies have found improvisation related activity in the alpha (8)(9)(10)(11)(12) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency range [7,16,45] located in prefrontal and medial frontal areas, while other studies have examined brain connectivity [32,49] or power changes at the sensor level [14,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…This prediction by phonetically congruent visual information can modulate early processing of the audio signal (Stekelenburg and Vroomen, 2007; Arnal et al, 2009; Pilling, 2009; Baart et al, 2014; Hsu et al, 2016; Paris et al, 2016a,b, 2017). Insight into the influence of multisensory experiences, such as musical training, is only beginning to unfold (Petrini et al, 2009a,b, 2011; Lee and Noppeney, 2011, 2014; Paraskevopoulos et al, 2012; Behne et al, 2013; Proverbio et al, 2016; Jicol et al, 2018), and how this regulates audiovisual modulation in speech is yet to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…Musical experience provides an attractive model for studying experience-based neural plasticity. Years of musical practice such as playing an instrument can enhance auditory processing (Zatorre et al, 2007; Strait and Kraus, 2014) and practicing a musical instrument offers a rich multimodal experience, integrating different sensory signals, including audio and visual information (Petrini et al, 2009a,b, 2011; Lee and Noppeney, 2011, 2014; Behne et al, 2013; Jicol et al, 2018). For example, a behavioral study by Petrini et al (2009a) showed that drummers, compared to non-musicians, were more sensitive to AV synchronicity for drumming point-light displays and can even perceptually replace missing visual information (Petrini et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%